Epigenome-wide association study of bronchopulmonary dysplasia in preterm infants: results from the discovery-BPD program - Wang, Xuting (2022)
Background: Bronchopulmonary dysplasia (BPD) is a lung disease in premature infants caused by therapeutic oxygen supplemental and characterized by impaired pulmonary development which persists into later life. While advances in neonatal care have improved survival rates of premature infants, cases of BPD have been increasing with limited therapeutic options for prevention and treatment. This study was designed to explore the relationship between gestational age (GA), birth weight, and estimated blood cell-type composition in premature infants and to elucidate early epigenetic biomarkers associated with BPD.Methods: Cord blood DNA from preterm neonates that went on to develop BPD (n = 14) or not (non-BPD, n = 93) was applied to Illumina 450 K methylation arrays. Blood cell-type compositions were estimated using DNA methylation profiles. Multivariable robust regression analysis elucidated CpGs associated with BPD risk. cDNA microarray analysis of cord blood RNA identified differentially expressed genes in neonates who later developed BPD.Results: The development of BPD and the need for oxygen supplementation were strongly associated with GA (BPD, p < 1.0E−04; O2 supplementation, p < 1.0E−09) and birth weight (BPD, p < 1.0E−02; O2 supplementation, p < 1.0E−07). The estimated nucleated red blood cell (NRBC) percent was negatively associated with birth weight and GA, positively associated with hypomethylation of the tobacco smoke exposure biomarker cg05575921, and high-NRBC blood samplesdisplayed a hypomethylation profile. Epigenome-wide association study (EWAS) identified 38 (Bonferroni) and 275 (false discovery rate 1%) differentially methylated CpGs associated with BPD. BPD-associated CpGs in cord blood were enriched for lung maturation and hematopoiesis pathways. Stochastic epigenetic mutation burden at birth was significantly elevated among those who developed BPD (adjusted p = 0.02). Transcriptome changes in cord blood cells reflected cell cycle, development, and pulmonary disorder events in BPD.Conclusions: While results must be interpreted with caution because of the small size of this study, NRBC content strongly impacted DNA methylation profiles in preterm cord blood and EWAS analysis revealed potential insights into biological pathways involved in BPD pathogenesis.